Effect of 2-Aminoethoxydiphenyl Borate on the State of Skeletal Muscles in Dystrophin-Deficient mdx Mice - Mikhail V. Dubinin; Anastasia E. Stepanova; Anastasia D. Igoshkina; Irina B. Mikheeva; Eugeny Yu. Talanov; Alena A. Cherepanova; Konstantin N. Belosludtsev (Frontiers in Bioscience-Landmark)
Objective: Ca2+ overload of muscle fibers is one of the factors that secondarily aggravate the development of Duchenne muscular dystrophy (DMD). The purpose of this study is to evaluate the effects of the Ca2+ channel modulator 2-aminoethoxydiphenyl borate (APB) on skeletal muscle pathology in dystrophin-deficient mdx mice. Methods: Mice were randomly divided into six groups: wild type (WT), WT+3 mg/kg APB, WT+10 mg/kg APB, mdx, mdx+3 mg/kg APB, mdx+10 mg/kg APB. APB was administered intraperitoneally daily for 28 days. Finally, we assessed the grip strength and hanging time of mice, the histology and ultrastructure of the quadriceps, as well as the parameters reflecting quadricep mitochondrial function. Results: 3 mg/kg APB was shown to reduce creatine kinase activity in the serum, intensity of degeneration and the level of fibrosis in the quadriceps of mdx mice, and improved tissue ultrastructure. However, this effect of APB was not sufficient to improve grip strength and hanging time of mdx mice. The effect of 3 mg/kg APB may be due to improve Ca2+ homeostasis in skeletal muscles, as evidenced by a trend toward decreased Ca2+ overload of quadricep mitochondria. High dose of APB (10 mg/kg body weight) showed less pronounced effect on the pathological phenotype of mdx mice. Moreover, 10 mg/kg APB disrupted the ultrastructure of the quadriceps and caused a decrease in grip strength in WT mice. Conclusions: APB is able to improve the phenotype in mdx mouse DMD model. However, the effect of APB is quite limited, which may be due to its multitargeting of Ca2+ channels in the membranes of muscle fibers and intracellular organelles, differentially expressed in DMD.